Preliminary Study on the Co-Location Offshore Wind and Wave Farms in Zhejiang Province - Jiang, Bo; Ding, Jie; Fang, Yizhou; Wu, Guowei; Wang, Xiaoyong; Ke, Shitang; Li, Ye; Hou, Erhu; Zheng, Chongwei; Zhou, Hongli; Wang, Meng; Bi, Dayong; et al. (Frontiers in Energy Research, 2022)
With the commercialization of offshore wind and the continued advancement of wave energy technologies, the option of locating both in the same sea area has emerged. The joint development of offshore wind and wave energy can effectively address the challenges faced by offshore wind and wave energy development, reduce costs, and improve the stability of power generation and output. This article introduces the current status of sea area utilization and marine functional zoning in Zhejiang Province and proposes a site selection method to identify the most suitable sea area for the construction of co-located offshore wind and wave farms in Zhejiang. First, a geographic information systems database was developed to identify unsuitable areas for co-located offshore wind and wave farms. Then, a literature review was conducted to establish a system of resource, economic, and technical selection indicators, and the Delphi method was used to determine the weight of each indicator. Finally, the sea areas suitable for the construction of co-located offshore wind and wave farms were evaluated and ranked, and the order of power plant development was given. The results of the study illustrate the potential of developing co-located offshore wind and wave farms in Zhejiang, especially in the northern part of Zhoushan and the southern part of Taizhou.